2016
DOI: 10.1016/j.pharep.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide inhibits endothelial nitric oxide formation and receptor ligand-mediated Ca2+ release in endothelial and smooth muscle cells

Abstract: H2S antagonized Ca(2+) mobilization by receptor agonists and store-operated Ca(2+) entry thereby limiting eNOS activation and NO formation. The effect of H2S on Ca(2+) stores was not restricted to endothelial cells but was also observed in vascular and tracheal smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…It has been suggested that H 2 S and NO are required in endothelium-dependent vasorelaxation in isolated aortic ring (Coletta et al, 2012). In human endothelial cells and smooth muscle cells from rat aorta, H 2 S limited the formation of NO (Kloesch et al, 2016). Accordingly, in the present study a negative correlation between the NO and H 2 S groups was observed in the male group.…”
Section: Discussionsupporting
confidence: 55%
“…It has been suggested that H 2 S and NO are required in endothelium-dependent vasorelaxation in isolated aortic ring (Coletta et al, 2012). In human endothelial cells and smooth muscle cells from rat aorta, H 2 S limited the formation of NO (Kloesch et al, 2016). Accordingly, in the present study a negative correlation between the NO and H 2 S groups was observed in the male group.…”
Section: Discussionsupporting
confidence: 55%
“…; Kloesch et al. ; Blatter ), and autonomic neurotransmitters such as norepinephrine (Garssen et al. ) that affect ASM.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study carefully investigated the influence of cholinergic nerves which play a predominant role, it is worth noting that other cell types, such as airway epithelial cells (Vanhoutte 2013) and sympathetic nerves (van Nieuwstadt et al 1994), can release factors in response to chemical depolarization that influence contractility of tracheal smooth muscle cells. These are factors released from tissue such as prostaglandins and nitric oxide (Ruan et al 2011;Kloesch et al 2016;Blatter 2017), and autonomic neurotransmitters such as norepinephrine (Garssen et al 1990) that affect ASM. Under conditions where we attempted to isolate depolarization-mediated effects, then 0 calcium external solution would be expected to prevent depolarization-induced secretion of these factors or sympathetic neurotransmitter release (Atlas 2001).…”
Section: Zero Ca2 + External Solution and Nifedipine Isolates Contracmentioning
confidence: 99%
“…It can also directly boost eNOS activity through S-sulfhydration, and by promoting endothelial influx of calcium via activation of TRPV1 channels 41 46. However, as a countervailing effect, H 2 S can inhibit endothelial eNOS activation by certain agonists owing to its ability to suppress inositol-1,4,5-triphosphate-mediated release of calcium from intracellular stores 51 52. The same mechanism opposes vasoconstriction of smooth muscle and platelet aggregation 52.…”
Section: Endogenous Hydrogen Sulfide Production Confers Versatile Carmentioning
confidence: 99%